EFEK ELECTRO THERAPY TRABERT CURRENT AND PULSE BURST KNEE OSTEOARTHRITIS PAIN GRADE II - Decintan, Windha Nurachma; Pristianto, Arif; Santosa, Totok Budi (Universitas Muhammadiyah Surakarta, 2021)
Background: osteoarthritis has fairly high prevalence of around 2.3% to 11.3%. Osteoarthritis is a degenerative disease which attacks the cartilage to the synovial joint. The problems that rise frequently are pain and discomfort. One of the physiotherapy actions that can be done in cases of osteoarthritis in reducing pain is using Transutaneus Electrical Nerve Stimulation (TENS) flow trabert. To find out the results of reducing pain and activity ability after being given therapy using the WOMAC measuring instrument. Objectives : (1) deternine the effect of TENS trabert current in cases of knee osteoarthritis, (2) find out the results of the effect of reducing pain with the WOMAC measuring instrument for a month. Method : The research type is using quasi-experimental with pre-post with control group. samples taken by consecutive sampling technique Research Results: there is an effect between both trabert current and pulse burst on the reduction of knee osteoarthritis pain. However, pulse burst is more effective than trabert current in reducing pain. The sensation feeling in the pulse burst is also more comfortable than the Trabert current. Conclusion : there is an effect of reducing pain after being given physiotherapy measures in the form of TENS trabert current.